2016
DOI: 10.1159/000447909
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Growth Hormone on Lipid Accumulation or Maturation in Adipocytes

Abstract: Background: Adipogenesis of adipocytes includes two stages: initiation and maturation. Growth hormone (GH) secretion is decreased in obese subjects and GH levels are inversely correlated with abdominal fat mass. The effects of growth hormone (GH) on lipids accumulation or maturation of adipocytes remains elusive. Methods: In the present study, effect of GH on lipid accumulation in vitro and in vivo was examined. cDNA microarray, quantitative real time-PCR (qPCR) and western blotting was used to analyze the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Total RNA was extracted using E.Z.N.A.® Total RNA kit according to manufacturer's instruction (OMEGA Bio‐Tek, VWR), quantified by Quanti‐iT TM RNA assay kit QUBIT (Invitrogen, Milan, Italy), and reverse transcripted with M‐MLV Reverse Transcriptase. Quantitative real‐time polymerase chain reaction (PCR; Applied Biosystems 7300 Real‐Time PCR System, CA, USA) coupled with SYBR green (SYBR green JumpStart Taq Ready Mix) was performed for identification of mRNA levels of IL6 (FW 5′‐GATGGATGCTACCAAACTGGAT‐3′, RV 5′‐CCAGGTAGCTATGGTACTCCAGA‐3′; Tsujimura et al, ), AdipoQ (FW 5′‐TGTTCCTCTTAATCCTGCCCA‐3′, RV 5′‐CCAACCTGCACAAGTTCCCTT‐3′), and FABP4 (FW 5′‐AAGGTGAAGAGCATCATAACCCT‐3′, RV 5′‐TCACGCCTTTCATAACACATTCC‐3′; Zhang et al, ). 18S rRNA (FW 5′‐GTAACCCGTTGAACCCCATT‐3′, RV 5′‐CCATCCAATCGGTAGTAGCG‐3′; Lood et al, ) was used as reference gene.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted using E.Z.N.A.® Total RNA kit according to manufacturer's instruction (OMEGA Bio‐Tek, VWR), quantified by Quanti‐iT TM RNA assay kit QUBIT (Invitrogen, Milan, Italy), and reverse transcripted with M‐MLV Reverse Transcriptase. Quantitative real‐time polymerase chain reaction (PCR; Applied Biosystems 7300 Real‐Time PCR System, CA, USA) coupled with SYBR green (SYBR green JumpStart Taq Ready Mix) was performed for identification of mRNA levels of IL6 (FW 5′‐GATGGATGCTACCAAACTGGAT‐3′, RV 5′‐CCAGGTAGCTATGGTACTCCAGA‐3′; Tsujimura et al, ), AdipoQ (FW 5′‐TGTTCCTCTTAATCCTGCCCA‐3′, RV 5′‐CCAACCTGCACAAGTTCCCTT‐3′), and FABP4 (FW 5′‐AAGGTGAAGAGCATCATAACCCT‐3′, RV 5′‐TCACGCCTTTCATAACACATTCC‐3′; Zhang et al, ). 18S rRNA (FW 5′‐GTAACCCGTTGAACCCCATT‐3′, RV 5′‐CCATCCAATCGGTAGTAGCG‐3′; Lood et al, ) was used as reference gene.…”
Section: Methodsmentioning
confidence: 99%
“…GH influences adipocyte differentiation by both stimulatory and inhibitory effects. It is secreted from the anterior pituitary gland exerting critical metabolic effects through other substances that seem to mediate its action (Zhang et al, ); GH decreases fat mass, an effect probably mediated by its stimulation of lipolysis and inhibition of lipogenesis (Olarescu et al, ). However, the early studies by Howard Green group (Green, Morikawa, & Nixon, ; Morikawa et al, ) showed that GH has a direct action on 3T3‐F442A clone inducing their differentiation into fat cells.…”
Section: Adipogenic Factorsmentioning
confidence: 99%
“…The expressions of these three genes in the liver of Group VitD+DM were significantly higher than Group T2DM, but the TG content is significantly reduced, so it also indirectly confirms that VitD can reduce the TG content in the liver tissue. When AdipoR2 is upregulated, it will activate the PPAR-α signaling pathway and act on the glucose and lipid metabolism-related enzymes, thereby enhancing the liver uptake of glucose 17 . Anderson also demonstrated that the activation of p38MAPK can prevent the accumulation of fat in the liver under high-fat feeding conditions 18 .…”
mentioning
confidence: 99%